Implementasi Kebijakan Pembiayaan Pendidikan Gratis pada SMK Negeri 1 Paringin Kabupaten Balangan (Studi Perda Nomor 2 Tahun 2010 tentang Pendidikan) - Ali Ridho (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The Implementation of Free Education Financing Policy at SMK Negeri 1 Paringin Balangan Regency (Study of Perda No. 2 of 2010 on Education). The purpose of this study was to determine: (1) the implementation of free education finance policy at SMK Negeri 1 Paringin Balangan regency, with reference to the provisions on the financing of education in the law, (2) the factors supporting and inhibiting a successful implementation financing policy of free education at SMK Negeri 1 Paringin Balangan regency. The research method in this study is a qualitative method with a case study approach. The results of the research that has been done is: (1) the implementation of free education finance policy at SMK 1 Paringin Balangan regency by the law as a whole has been implemented and achieved well with approximately 78.5% achievement rate, (2) the factors to be supporting goals or objectives are clear and consistent policies, the implementation process has a clear legal basis in order to ensure compliance officers happened on the field and target groups, the commitment and expertise of the policy implementers, stakeholders and support the stability of the social, economic and political. While inhibiting factor is the lack of a strong theoretical support in formulating policy.